PENGEMBANGAN MODUL PEMBELAJARAN IPA BERBASIS GROUP DISCOVERY LEARNING (GDL) UNTUK MENINGKATKAN NILAI KOGNITIF BAGI SISWA MADRASAH TSANAWIYAH - Fitri Nur Istikomah; Anak Agung Oka; Triana Asih (EDUBIOLOCK, 2022)
Learning science using Group Discovery Learning (GDL) will help the learning process because this learning can train students to learn actively and independently in a learning process. The results of interviews with subject teachers showed that there are no modules, only LKS and a limited number of Package Books. Many students learning outcomes have not reached the KKM standard value. From the results of the interviews, researchers will develop a GDL-based module as a learning resource to improve students' cognitive learning outcomes. This study aims to produce learning tools developed, namely GDL-based modules, to enhance students' cognitive values by using modules in class VII MTs Riyadlatul Ulum. This type of research is the development of a Science Learning Module based on Group Discovery Learning using the 4D development model, Define, Design, Develop and Disseminate, suggested by Thiagarajan and Sammel. The analysis results from the design expert test were 95%, the material expert test was 85%, and the student response test was 89%. The results of the discussion regarding the development of the module can be concluded that before the development of the completeness module, students were only 33%. Still, after using the module, the first meeting increased by 70% and to 87% at the second meeting. So the module development is feasible to be used and used as a science learning resource and can improve students' cognitive learning outcomes.